EVALUATION OF CASTOR BEAN GENOTYPES SUBMITTED TO DIFFERENT FERTILIZATION LEVELS - Pivetta, Laerte Gustavo; Zanotto, Mauricio Dutra [UNESP]; Tomaz, Camila De Aquino [UNESP]; Pivetta, Laercio Augusto; Da Costa Lara Fioreze, Ana Carolina; Zoz, Tiago (Univ Estadual Mato Grosso Sul, 2015)
A study was conducted to evaluate the response of the castor bean hybrids of UNESP/FCA Breeding Program and commercial cultivars submitted to different fertilization levels. The experimental was arranged in a randomized blocks design, in a 4x4 factorial, composed of four castor bean genotypes [two hybrids (A and B) and two cultivars (FCA-PB and IAC 2028)] and four fertilization levels (0, 50, 100 and 150% of the recommended rate based on soil analysis). The IAC 2028 cultivar had the lower number of racemes per plant, but had the highest number of grains per raceme, mass of 100 grains and grain yield. The increase in fertilization levels increased all the yield components and the grain yield. The results suggest that fertilizer application above the recommended rate promotes increased grain yield and higher profits in the production of castor beans.
Keywords: Hybrids; cultivars; mechanical harvesting